Improving Student Character Through Scout Extracurriculars With A Lesson Study Model - Risky Dwi Cahya; Suzana; Romi Febri; Lisna Arfika; Ratih Oktavia (Jurnal Edukasi, 2023)
This research focuses on improving the character of students post-covid pandemic through extracurricular scouting. This research was conducted at SD Negeri 9 Manggar. The subject of the study was a student consisting of 30 students. This type of research is school action research or PTS. Data collection techniques use observation, interviews, pretests and postests as well as questionnaires. Data processing using percentage formulas. The results of the research on scout extracurricular Recovery activities in improving student character education started from the results of teacher satisfaction with the development of student attitudes with a score of 3.33 in the satisfied category. Based on the discussion of the results of research conducted, scout extracurricular activities in improving student character education are seen from the results of teacher satisfaction with the development of student attitudes with a score of 3.33 in the satisfied category. Based on the results of research in student activities in cycle 1 with an attitude value of 68.74% with sufficient criteria (C) and a knowledge value of 66.32% with sufficient criteria (C). in cycle 2 with an attitude value of 87.50% with a Good criteria (B) and a knowledge value of 81.32% with a Good criteria (B)